Meeting the Needs of the Stakeholders: Qualifications for Graduates of Teacher Training and Education - Mustapha, Prof. Dr. Ramlee (Sebelas Maret University, 2016)
The impact of globalization on teacher education is unprecedented. Changing in the global education landscape has transform the theory-practice nexus in teacher education. Another revolution is needed to transform educational system and prepare graduates for the 21st century realities.Â Drawing on the perspectives of the stakeholders and focusing on digital learners are pertinent to bring teacher education onto a higher level of excellence.Â In the new millennium, education must focus on the whole child â morally, intellectually, physically, socially and aesthetically.Â In meeting the needs of the stakeholders, authentic learning, multi-literacies, innovative thinking and research-based improvements are keys to the 21st century teacher education model.Â Authentic learning typically focuses on real-world, complex problems and their solution using role-play exercises, problem-based activities, case studies, and participation in virtual communities of practice. The learning environments are inherently multidisciplinary, thus, authentic learning could be a dynamic tool to enhance learning and to provide opportunities for students to engage in higher-order thinking and active learning.Â Leading high performing teacher education system is also critical. Educational leaders need to focus on seeking new innovative models of teacher education, pedagogy and learning, and support services. World-class teacher education program could attract best students. In order to raise teachers and studentsâ competencies and standards, it is not enough to declare high performing schools; it is critical to develop thinking and well-rounded students who are the future high performing thinkers and innovators.Â For the innovation culture to flourish, granting flexibility and autonomy is a way of moving forward.Â To gain international recognition, the development of transnational standards for teacher education and training with a multidisciplinary and innovative orientation is critical.Â Hence, a country needs a dynamic and resilient teacher education framework or a roadmap for producing quality teachers in the context of sustainable development.